Evaluación de los animales en base a los caracteres de importancia económica en la producción de leche de bovinos acorde al objetivo de mejora genética en la parroquia Cusubamba - Vargas Naula, Johanna Lissette (2023)
Genetic improvement programs allow us to improve milk production, reduce production costs, therefore, help us increase the profitability of dairy activity. In the parish of Cusubamba located in the Salcedo canton, province of Cotopaxi, producers face challenges in milk production due to the lack of adequate food resources, inadequate management due to lack of knowledge and the climate, these factors trigger the presence of animals in suboptimal conditions, low milk production and reproductive problems. The research project aims to improve milk production in cattle through genetic improvement and artificial insemination. The research was carried out with 10 producers in two neighborhoods of the parish of Cusubamba, data was collected from 148 cattle. Data on owners and cattle were collected, including productive, reproductive, nutritional and health aspects. Information was taken regarding weighing, production data, milk weight, density, and clinical mastitis tests (CMT) were also performed.